Parcel Fragmentation and Land Consolidation - Air, Bharat Singh; Ghimire, Moti Lal (Journal on Geoinformatics, Nepal, 2016)
Parcel Fragmentation is the division of parcel into smaller pieces having individual ownership. The main parameters used for measurement of Parcel Fragmentation have been considered the spatial location of parcel, shape & size of parcel and number of parcel. The main causes of Parcel Fragmentation are; inheritance, population growth, land market, historical/ cultural perspective, personal prestige & status, economic & physical process, quality of soil and physical condition of parcels. The main impacts seen due to the Parcel Fragmentation are as reduction of agricultural production, increases of agricultural production cost, increases land disputes, increases transport cost, wasted time for the workers travelling, supervision, securing & management, reduce parcel area due to walls & fences and cannot use modern equipment in agricultural activities. Land Consolidation is the reverse act of Parcel Fragmentation. It is the process of formation of single or individual parcel by merging several parcels having enough size& suitable shape and helps to reduce those impacts which are seen in the fragmented parcels so it is profitable to move in the direction of Land Consolidation.